The Active Labor Market Policy and its Impact on Youth Employment - Apostolov, Valeri (Research Papers, 2019)
This article assesses a significant economic and social problem – youth integration in the labour market. The aim of this research is to expose the actual condition of the impact of public policies and measures for the promotion of youth employment, emphasizing the connection between the education system and the labour market. For the purpose has been done a content analysis of the normative acts and documents, examples of good practices of public policies and measures in support of the professional realization of young people in the labour market have been also given. As a result of the analysis of the market’s condition and the implementation on a national level of European Youth Guarantee have been made conclusions, evaluations, and recommendations.